EFFECT OF CLIPPING AND GRAZING ON VARIOUS VEGETATIONAL PARAMETERS OF GRASSLAND COMMUNITIES IN BUNDELKHAND REGION (U.P.) - NEEL RATAN; R. K. GUPTA; U. N. SINGH (The Bioscan, 2011)
Two grassland communities of Bundelkhand region, one on the managed (periodically clipped) and protected site of G.I.C. ground (site I) and the other moderately grazed, open natural site of D.V. (P.G.) College Campus (site II) were selected and analysed for the comparison of various vegetational parameters. Out of the total 46 species, 19 were common to both sites, 7 species occurred exclusively at site I and 20 species at site II. The majority of the species at both the sites were fortuitous. On managed site, only a few species showed high values of phytosociological indices while open natural and moderately grazed site showed more even distribution of values. Upper strata species like Desmostachya bipinnata, Fimbristylis dichotoma and Vernonia cinerea were rare in abundance at managed site while Chrysanthellum indicum, Dactyloctenium aegypticum and Cassia tora were rare at natural site. The community at site I showed markedly higher dominance and the lower diversity and evenness values as compared to those at site II. A high species turnover of 8.8 indicates considerable differences between the managed and natural sities with respect to species richness and population size of key species.